Neighbourhood-based social integration. The importance of the local context for different forms of resource transfer - Farwick, Andreas; Hanhörster, Heike; Lobato, Isabel Ramos; Striemer, Wiebke (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
Due to their lack of financial resources, poor residents of deprived neighbourhoods are very much reliant on support and assistance from their personal networks. Studies refer to the key importance of neighbourhood contacts transcending social boundaries to promote upward social mobility. Based on a mix of quantitative and qualitative findings, this paper looks at the importance of social mix within a person’s neighbourhood and immediate surroundings for transferring different kinds of resources. The results show that even residents of deprived neighbourhoods can call on a well-developed support network to deal with everyday problems. The contribution also shows that network contacts to people endowed with more resources are no guarantee for the upward social mobility of the less well endowed. Indeed, it would seem that ‘getting-ahead’ resources are also accessible via their homogeneous networks. Much more to the point, the immediate surroundings turn out to be an important spatial context for contacts and resource transfers, especially for families with children.